COVID-19 related risk perception among taxi operators in Kingston and St. Andrew, Jamaica. (September 2021) - James, Kenneth; Thompson, Camelia; Chin-Bailey, Cameal; Davis, Kayon Donaldson; Nevins, Desmalee Holder; Walters, Dawn
Abstract: Background: In the Caribbean, all countries have confirmed COVID-19 cases. Considering the high infectivity of the virus, no preexisting immunity to the virus and an associated modest reproductive rate (R0 ), the high density of persons utilizing public transport is of immense public health concern. Public transport systems may facilitate and accelerate the transmission of the disease. Aim: The aim of this study was to assess the COVID-19 related risk perceptions among taxi drivers by virtue of their occupation and the implications for health promotion interventions. Methods: A cross-sectional study was conducted in May 2020 among 282 taxi drivers in the Kingston and St. Andrew (KSA) metropolitan region in Jamaica. A 28-item anonymized self-administered questionnaire was used to collect data which was subsequently analyzed using SPSS version 20. A risk score was generated and the Mann-Whitney U and Kruskal Wallis tests were used to determine differences in the mean ranks for risk perception score as applicable. A 5% alpha level was utilized in determining statistical significance. Results: Risk perception scores ranged from 10 to 21 with a median of 17 (IQR 3.25) and there was no statistically significant difference in the median risk perception score by socio-demographic variables. There was however, a statistically significant positive correlation (Spearman's rho = 0.238, p=<0.001) between risk perception and knowledge. Approximately, 86% of respondents reported that they obtained COVID-19-related information from news reports (traditional media). Conclusion: Taxi drivers perceive themselves to be at occupationally related risk of COVID-19. Therefore, greater understanding of this issue is paramount as it can aid in the crafting of initiatives that may enhance personal safety of both taxi drivers and commuters. Highlights: Taxi operators perceive themselves to be at occupationally related risk of COVID-19. Taxi drivers with higher knowledge scores had higher risk perception scores. Most respondents obtained COVID-19-related information from news reports (traditional media).